2018
DOI: 10.1002/ags3.12057
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular invasion of single small hepatocellular carcinoma ≤3 cm: Predictors and optimal treatments

Abstract: BackgroundSmall hepatocellular carcinomas (HCC ≤3 cm) are generally considered to have low malignant potential; however, some of them display pathological microvascular invasion (MVI).MethodsBetween 1991 and 2013, 414 patients with a single HCC ≤3 cm underwent curative hepatic resection (HR). Predictors for MVI were identified. Using another cohort (149 patients during 2000‐2014), our predictors for MVI in HCC ≤3 cm were validated. In 428 patients with a single HCC ≤3 cm who had predictors for MVI, survival wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…Recent studies have demonstrated that tumor diameter, tumor number, degree of differentiation and serum level of prothrombin induced by vitamin K absence-II (PIVKA-II) were predictors of MVI [ 6 ]. One study reported that independent predictors of MVI included tumor diameter > 2 cm, alpha-fetoprotein (AFP) > 200 ng/mL and PIVKA-II > 40 mAU/mL [ 7 ]. Previous research has reported that the incidence of MVI ranged from 15 to 57% in HCC specimens and was associated with tumor size, AFP and typical imaging features [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that tumor diameter, tumor number, degree of differentiation and serum level of prothrombin induced by vitamin K absence-II (PIVKA-II) were predictors of MVI [ 6 ]. One study reported that independent predictors of MVI included tumor diameter > 2 cm, alpha-fetoprotein (AFP) > 200 ng/mL and PIVKA-II > 40 mAU/mL [ 7 ]. Previous research has reported that the incidence of MVI ranged from 15 to 57% in HCC specimens and was associated with tumor size, AFP and typical imaging features [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most signi cant reason for the dismal prognosis is vascular invasion. Previous research has demonstrated that vascular invasion is a vital risk factor for the prognosis of HCC patients after curative hepatectomy [31]. Disappointingly, routine diagnostic methods are unable to identify the HCC patient subpopulation at high risk of having microvascular invasion preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that tumor diameter, tumor number, degree of differentiation and serum level of prothrombin induced by vitamin K absence-II (PIVKA-II) were predictors of MVI [7,8]. A study reported that independent predictors of MVI were tumor diameter >2 cm, alphafetoprotein (AFP) >200 ng/mL and PIVKA-II >40 mAU/ml [9]. Previous research reported that the incidence of MVI ranged from 15% to 57% in HCC specimens and was associated with tumor size, AFP and typical image features [10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the NxS factor can be obtained from imaging modalities such as computed tomography (CT) or magnetic resonance imaging (MRI), and information on pathological vessel involvement is not needed. Although vascular invasion, one of the TNM staging components, is considered a prognostic factor, a peripheral vascular invasion is usually observed as microvascular invasion in the resected specimen and underestimated preoperatively (29,30). Thus, unsuccessful preoperative assessment causes a potential limitation in the TNM and TNM-based systems due to the discrepancy between the pre-and postoperative status of HCC patients.…”
Section: Discussionmentioning
confidence: 99%